Witches of Brooklyn. 1 - Escabasse, Sophie (Random House Graphic, 2020)
Effie's life is turned upside down when she moves to Brooklyn to live with her weird aunts. There, she soon learns that magic runs in her family, and she and her aunts are witches. When a cursed popstar comes looking for their help, Effie and her aunts are in for a wild ride.